FLOODS, ENVIRONMENTAL CONDITIONS, AND THEIR ROLE IN TRIGGERING DENGUE FEVER EPIDEMICS (Journal of Medical & Health Sciences Review, 2025)
Floods represent one of the key environmental factors leading to dengue fever outbreaks due to the fact that they lead to the emergence of stagnant water, which is a perfect breeding place of the Aedes aegypti and Aedes albopictus, which are the vectors of the dengue virus. Besides boosting the growth of mosquitoes, flooding undermines the mosquito control strategies, destroys the health infrastructure of the populations, and displaces the populations to the crisis shelters or overcrowded places, thus exposing people to close contact with mosquitoes and the rapid spread of the virus. The environmental factors that exacerbate the magnitude of the post-flood dengue outbreaks include temperature, humidity, urbanization, and socioeconomic conditions. To be effective, prevention and control must involve complex interventions that are a combination of environmental management (drainage enhancement, waste disposal, safe water storage), infrastructure development (flood-resistant housing, urban planning), community involvement (awareness campaign, source reduction, personal protection), and well-developed surveillance systems based on predictive simulation and early warning systems. These interventions are necessary to mitigate the occurrence of dengue and curb epidemic possibilities and support the resilience of the population in the flood-prone areas to the emerging disasters by involving active, adaptive, and coordinated actions at the local, provincial, and national levels, considering the ever-growing frequency and intensity of floods under climate change.